Revisiting the Past in the Age of Posts: Rememory in Toni Morrison's God Help the Child and Gisèle Pineau's Femmes des Antilles. (8th August 2020) - Gras, Delphine
Abstract: In this article, I examine how Toni Morrison and Gisèle Pineau provide timely pieces against the historical amnesia characteristic of post-racial discourse in the USA and in France. Studying Morrison's God Help the Child (2015) and Pineau's Femmes des Antilles: Traces et Voix (1998) side by side reveals how Morrison's rememory is a global concept as pertinent today as when first coined in Beloved (1987). The term's original use in the context of slavery also suggests a lens through which to read Morrison's non-slavery era works like God Help the Child . What ultimately comes to the fore in both authors' potent expositions of the specter of slavery haunting black women in the USA, France, and the West Indies is a rejection of historical silencing.